Single Nucleotide Polymorphisms of Transcription Factor 7-LIKE 2 Gene Expressed Different MRNA Isoforms in the Peripheral Blood - Made Ratna Saraswati; I Gusti Ngurah Kade Mahardika; Ketut Suastika; Sukma Oktavianthi; Herawati Sudoyo; Safarina G. Malik (Journal of Global Pharma Technology, 2018)
Background: Single Nucleotide Polymorphisms (SNPs) of the Transcription Factor 7-Like 2 (TCF7L2) diabetes susceptibility gene were located in the noncoding region. Intronic SNP may play a role in mRNA splicing. This study aimed to elucidate whether SNPs of the TCF7L2 gene expressed different mRNA isoforms in the peripheral blood. Methods: Across sectional study was conducted in Legian Bali. A total of 56 subjects were grouped into carrier of TCF7L2SNPs (28 Balinese age 30-74 years,eitherheterozygote or mutant of the rs12255372 SNP [GT or TT], rs7903146 [CT or TT], and rs10885406 [AG or GG])and wild-type of TCF7L2 (28 matched in age and sex Balinese,rs12255372 [GG], rs7903146 [CC], and rs10885406 [AA])which has been identified in the previous study.In this study, the mRNA isolation was done using LS Trizol reagent (Nitrogen®) and variants of the mRNA isoform in the TCF7L2 gene was identified by reverse transcriptase-polymerase chain reaction (RT-PCR) method, using two pairs of overlapping primer.The first primer PCR products were grouped into Group-A, Group-B, Group-C and Group-D. The second primer PCR products were grouped into Group-a, Group-b, Group-c and Group-d. Oral glucose tolerant test (OGTT) was done to both groups.Blood samples were taken during fasting, at 1 hour and 2 hours after the oralglucose load, for blood glucose, and insulin level measurement. Results: There were seven pairs of the group combination including group A-a, A-c, A-d, C-a, C-c, C-dand D-c, and group C-c was the most commonly found among all subjects in this study (42.3%). Subjects with diabetes risk allele were 2.66 times more likely to express group C-ccompared to subjects without diabetes risk allele of SNPs in the TCF7L2 gene (95%CI 1.24–5.72 p=0.011). Mean response of insulin increment after oral glucose load among group C-c was higher compared with the non-group C-c, 84.63±41.01 vs. 62.02±38.09ng/ml (mean difference 22.61 95%CI 0.41–44.80 p=0.046). However, blood glucose level, fasting insulin, HOMA %B and HOMA IR were similar between the two groups. Conclusion: Variants of TCF7L2 gene expressed different mRNA isoformsin the peripheral blood.Compared to subjects without diabetes risk allele of SNPs in the TCF7L2 gene, subject with diabetes risk allele expressed dominant variant isoform mRNA 2.66 timeshigher.The higherresponse of insulin increment after oral glucosewas observedin the dominant variant which may reflectthe early condition of insulin resistant.Keywords: Diabetes, SNP TCF7L2, isoforms mRNA.